On the feasibility of manufacturing glass with mining waste (Research, Society and Development, 2022)
Waste materials generated by mining have been mostly stored in dams or stockpiles, generating high costs for its management. The present work aimed, firstly, to verify the amenability of mining wastes as a raw material for the glass production, and to economically evaluate their use, citing the main features of the manufacture of glass, and simulating the implementation of a glass factory, meeting public policy guidelines for the use of solid waste. In a first stage, prospective laboratory tests, based on the literature review, showed the technical feasibility of using mining residues from the Ouro Preto region (MG, Brazil) for the manufacture of glass. Next, an expeditious appraisal of a silica-lime-soda glass factory was made for two production scenarios, namely: 15 t/day and 400 t/day. It is concluded by the economic viability of this type of enterprise, which, however, requires a large investment of capital, proving to be very valuable the support of government development agencies for its implementation.